Exploration and Antifungal Assay of Endophytic Fungi as Biocontrol of Onion Purple Blotch Disease Caused by Alternaria porri (Ell) Cif In Vitro - Wita Firdausi; Liliek Sulistyowati; Luqman Qurata Aini (AGRIVITA, Journal of Agricultural Science, 2021)
Purple blotch disease caused by Alternaria porri is the main destructive foliar disease of genus Allium, causing significant losses in yield of the crops. Recently, purple blotch disease is controlled by synthetic fungicides. However, fungicides have negative effects on the environment. Endophytic fungi can be used as an alternative control because a close symbiosis with the internal tissue of the host can minimize competition in new and complex ecosystems. This study aimed to explore and identify endophytic fungi that have the highest inhibition ability against A. porri and investigate the antagonistic mechanism. The method used in this study is an exploration of endophytic fungi, isolation of A. porri, in vitro antagonism tests, observation of the antagonistic mechanism, extraction of crude protein, SDS-PAGE, and identification. The antagonistic fungi that had the highest inhibition ability were identified as Penicillium citrinum with an inhibitory of 60.04%. Crude protein extracted from P. citrinum which showed inhibitory activity against A. porri is saturation level of ammonium sulfate 80% with a molecular weight of 40 kDa. This study implies that P. citrinum can inhibit the growth of A. porri through its anti fungi compounds. Further in vivo assays or field trials will need to be conducted in future studies.